Tongue function and swallowing in individuals with temporomandibular disorders (Journal of Applied Oral Science, 2021)
The tongue participates in the oral phase of swallowing by pushing the food bolus toward the oropharynx. This relationship between tongue function and swallowing is little addressed addressed in individuals with temporomandibular dysfunction (TMD). Objective: To analyze the association of functional tongue conditions on swallowing in individuals with TMD. Methodology: After approval by the Institutional Review Board, the study was conducted on 30 individuals of both sexes, aged 18 to 28 years, with TMD, and not treated for the disorder. Tongue function was assessed as to the mobility, pressure, and oral motor control. Swallowing was analyzed by clinical assessment during ingestion of solid (wafer biscuit) and liquid (water). Data regarding mobility and swallowing were collected using the orofacial myofunctional evaluation protocol. Tongue pressure was measured by the Iowa Oral Performance Instrument, during elevation, protrusion, swallowing, and resistance test. The oral motor control was assessed by the oral diadochokinesis (DDK) test by rapid and repeated emissions of syllables “ta” and “ka”. Data were statistically analyzed by the Spearman correlation coefficient, at a significance level of 5%. Results:Relationships were found between tongue function and swallowing for the following aspects: mobility (r=0.741), pressure in protrusion (r=-0.366), swallowing of saliva (r=-0.499), mean DDK rate in emissions “ta” (r=-0.424) and “ka” (r=-0.446), and mean DDK period in emissions “ta” (r=0.424) and “ka” (r=0.446). Thus, the greater the change in tongue mobility, the lower the tongue pressure in protrusion and swallowing of saliva, the lower the emissions per second, the longer the mean time between vocalizations, and the worse the swallowing of individuals with TMD. Conclusion: The functional conditions of the tongue regarding mobility, pressure, and oral DDK were associated with swallowing in individuals with TMD.